2021
DOI: 10.1590/1413-81232020261.02222019
|View full text |Cite
|
Sign up to set email alerts
|

O papel da autoeficácia parental na saúde mental de mães de crianças com Síndrome da Zika Congênita

Abstract: Resumo O artigo buscou avaliar o papel mediador da autoeficácia parental (AEP) entre os fatores socioambientais e a saúde mental das mães de crianças com síndrome da Zika congênita (SZC). Os fatores socioambientais foram operacionalizados a partir da avaliação cognitiva e afetiva que as pessoas fazem do seu contexto (Bem-estar subjetivo, BES) e da fadiga. Participaram deste estudo 69 mães de crianças com SZC, com média de idade de 26,4 anos, residentes no estado do Ceará. Foi aplicado um questionário contendo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 41 publications
1
2
0
1
Order By: Relevance
“…High or clinically relevant stress levels were found in 13% of the family caregivers investigated by Pereira et al 44 , who also observed a relationship between stress and job loss, corroborating the findings of Reis et al 41 . Women with high stress levels were five times more likely than those with normal levels to experience difficulties keeping a job and covering basic household expenses.…”
Section: Health Impactssupporting
confidence: 83%
See 2 more Smart Citations
“…High or clinically relevant stress levels were found in 13% of the family caregivers investigated by Pereira et al 44 , who also observed a relationship between stress and job loss, corroborating the findings of Reis et al 41 . Women with high stress levels were five times more likely than those with normal levels to experience difficulties keeping a job and covering basic household expenses.…”
Section: Health Impactssupporting
confidence: 83%
“…The cash benefit program Benefício de Prestação Continuada, introduced by the National Social Assistance Policy, was the main government benefit received by the families. However, some articles highlighted difficulties accessing this benefit 35,44 and Scott et al 20 mention that the eligibility criteria can affect other benefits/ income, such as pensions and work, given that working mothers are not eligible to receive the benefit.…”
Section: Economic and Materials Impactsmentioning
confidence: 99%
See 1 more Smart Citation
“…A autoeficácia parental tem relação com as crenças e julgamentos que os pais detêm das suas capacidades para organizar e executar um conjunto de tarefas relacionadas com a criação de uma criança. Isto consiste em dois aspectos: conhecimento específico de comportamentos parentais associados com a tarefa de criar uma criança e o nível de confiança dos pais em relação à sua habilidade de realizar esses comportamentos (6)(7)(8)(9).…”
Section: Introductionunclassified
“…Para isso, é fundamental garantir, além dos recursos materiais, recursos humanos como suportes ou apoios nesse processo. Estes incluem todos os profissionais e cuidadores que, no caso de crianças com a SCZV, tem se centrado na mãe, conforme evidenciaram várias pesquisas (AZEVEDO; FREIRE; MOURA, 2021;FLEISCHER;LIMA, 2020;SOUZA, 2021;MENEZES et al, 2018;MENDES, 2020). Promover programas de intervenção e comunicação alternativa tendo como centralidade a família (ou nesse caso a mãe), considerando a rotina e a realidade social da criança, tem se mostrado promissor na literatura científica internacional (ROSENBAUM; GORTER, 2012).…”
Section: Introdução E Aspectos Teóricosunclassified